FROM CHAOS TO CLARITY: HOW ENGLISH SYNTAX CREATES MEANING - Faqih Hibatulah Z; Ajrul Khair; Mhd Ilham Khanis; Maulana Budi Satria Siregar; M. Rafly Raja Gazali Nahulae (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This article examines the fundamental role of syntactic structure in constructing and determining meaning in the English language. Syntax is understood not merely as a set of formal rules, but as a cognitive framework that organizes lexical elements and transforms potential semantic chaos into clear and purposeful communication. This study employs a qualitative descriptive-analytical approach by using structured sentence examples to reveal the main syntactic mechanisms in English, particularly the relatively fixed word order of Subject–Verb–Object, hierarchical phrase structure, and the process of syntactic ambiguity resolution. The analysis shows that English syntax functions as a generative system that plays an important role in grammatical role assignment, the formation of complex propositions, and the creation of discourse cohesion. Furthermore, syntactic structure is proven to be a primary factor in meaning interpretation and sentence comprehension. These findings emphasize that mastery of syntactic principles is a crucial aspect in achieving clarity, accuracy, and effective communication, and has important implications for language teaching, academic writing, and linguistic studies in conceptual, pedagogical, and applicative dimensions within the context of modern English language learning in the global digital era. ABSTRAK Artikel ini mengkaji peran fundamental struktur sintaksis dalam membangun dan menentukan makna dalam bahasa Inggris. Sintaksis dipahami tidak sekadar sebagai seperangkat aturan formal, melainkan sebagai kerangka kognitif yang mengorganisasi unsur leksikal sehingga mampu mengubah potensi kekacauan makna menjadi komunikasi yang jelas dan terarah. Penelitian ini menggunakan pendekatan kualitatif deskriptif-analitis dengan memanfaatkan contoh-contoh kalimat terstruktur untuk mengungkap mekanisme sintaksis utama dalam bahasa Inggris, khususnya urutan kata yang relatif tetap Subject–Verb–Object, struktur hierarkis frasa, serta proses penyelesaian ambiguitas sintaktis. Hasil analisis menunjukkan bahwa sintaksis bahasa Inggris berfungsi sebagai sistem generatif yang berperan penting dalam penentuan peran gramatikal, pembentukan proposisi kompleks, serta penciptaan kohesi wacana. Selain itu, struktur sintaksis terbukti menjadi faktor utama dalam penafsiran makna dan pemahaman kalimat. Temuan ini menegaskan bahwa penguasaan prinsip-prinsip sintaksis merupakan aspek krusial dalam mencapai kejelasan, ketepatan, dan efektivitas komunikasi, serta memiliki implikasi penting bagi pengajaran bahasa, penulisan akademik, dan kajian linguistik secara konseptual, pedagogis, dan aplikatif dalam konteks pembelajaran bahasa Inggris modern di era global digital.